Induction of thyroid gene expression and radioiodine uptake in melanoma cells: novel therapeutic implications. - Peng Hou (PLoS ONE, 2009)
Both the MAP kinase and PI3K/Akt pathways play an important role in the pathogenesis of melanoma. We conducted the present study to test the hypothesis that targeting the two pathways to potently induce cell inhibition accompanied with thyroid iodide-handling gene expression for adjunct radioiodine ablation could be a novel effective therapeutic strategy for melanoma. We used specific shRNA approaches and inhibitors to individually or dually suppress the MAP kinase and PI3K/Akt pathways and examined the effects on a variety of molecular and cellular responses of melanoma cells that harbored activating genetic alterations in the two pathways. Suppression of the MAP kinase and PI3K/Akt pathways showed potent anti-melanoma cell effects, including the inhibition of cell proliferation, transformation and invasion, induction of G(0)/G(1) cell cycle arrest and, when the two pathways were dually suppressed, cell apoptosis. Remarkably, suppression of the two pathways, particularly simultaneous suppression of them, also induced expression of genes that are normally expressed in the thyroid gland, such as the genes for sodium/iodide symporter and thyroid-stimulating hormone receptor. Melanoma cells were consequently conferred the ability to take up radioiodide. We conclude that dually targeting the MAP kinase and PI3K/Akt pathways for potent cell inhibition coupled with induction of thyroid gene expression for adjunct radioiodine ablation therapy may prove to be a novel and effective therapeutic strategy for melanoma.